Domains of cognitive function in early old age: which ones are predicted by pre-retirement psychosocial work characteristics - Sabbath, Erika L; Andel, Ross; Zins, Marie; Goldberg, Marcel; Berr, Claudine (Occupational and environmental medicine, 2016)
BACKGROUND: Psychosocial work characteristics may predict cognitive functioning after retirement. However, little research has explored specific cognitive domains associated with psychosocial work environments. Our study tested whether exposure to job demands, job control and their combination during working life predicted post-retirement performance on eight cognitive tests. METHODS: We used data from French GAZEL cohort members who had undergone post-retirement cognitive testing (n=2149). Psychosocial job characteristics were measured on average for 4 years before retirement using Karasek's Job Content Questionnaire (job demands, job control and demand-control combinations). We tested associations between these exposures and post-retirement performance on tests for executive function, visual-motor speed, psychomotor speed, verbal memory, and verbal fluency using ordinary least squares regression. RESULTS: Low job control during working life was negatively associated with executive function, psychomotor speed, phonemic fluency and semantic fluency after retirement (p's<0.05), even after adjustment for demographics, socioeconomic status, health and social behaviours and vascular risk factors. Both passive (low-demand, low-control) and high-strain (high-demand, low-control) jobs were associated with lower scores on phonemic and semantic fluency when compared to low-strain (low-demand, high-control) jobs. CONCLUSIONS: Low job control, in combination with both high and low-job demands, is associated with post-retirement deficits in some, but not all, cognitive domains. In addition to work stress, associations between passive work and subsequent cognitive function may implicate lack of cognitive engagement at work as a risk factor for future cognitive difficulties.
Keywords: Surveys and Questionnaires; pracoviště; pracovní zátěž; Humans; neuropsychologické testy; lidé středního věku; Retirement; kognice; Occupational Diseases; kohortové studie; Female; rizikové faktory; Aged; práce; Workplace; stárnutí; nemoci z povolání; senioři; lidé; Aging; Regression Analysis; průzkumy a dotazníky; Cohort Studies; Francie; France; Stress, Psychological; důchod; společenská třída; Work; Neuropsychological Tests; ženské pohlaví; Male; Workload; Middle Aged; Cognitive Dysfunction; psychický stres; Social Class; mužské pohlaví; Cognition; kognitivní dysfunkce; regresní analýza; Risk Factors